Italian military internees in Stalag-352 Nazi camp in Masjukowshchyna (1943–1944) - Marozau, Dzmitry V.; Bordignon, Edoardo (Journal of the Belarusian State University. History, 2021)
The article analyses the Belarusian and foreign historiography of the problem of finding Italian internees in Masjukowshchyna in 1943–1944. The authors introduce new information into scientific circulation, relying on the personal archive of E. Bordignon, whose own grandfather was in Stalag-352 as a prisoner. The living conditions of the Italian prisoners of war are considered, as well as information about their further fate on the example of Domenico Arzani.
Keywords: Stalag-352; Masjukowshchyna; Italian military internees; Great Patriotic War; occupation; Soviet prisoners of war; victims of Nazism; places of memory; Minsk; local history; Memory; responsibility and future foundation